Pengaruh Dow Jones Islamic Market Industrials dan US Dollar Index Future terhadap Indeks Saham Syariah Indonesia - Midesia, Shelly (Jurnal Investasi Islam, 2022)
Knowing the movement of Indonesia Sharia Stock Index is indispensable for capital market investors in their decision-making steps. This study aims at determining the effect of Dow Jones Islamic Market Industrials and US Dollar Index Future on Indonesia Sharia Stock Index. The data used in the research are daily close price of Indonesia Sharia Stock Index, Dow Jones Islamic Market Industrials and US Dollar Index Future in 2021. Regression analysis were used for data analysis, using SPSS data processing tool. The result indicates that Dow Jones Islamic Market Industrials and US Dollar Index Future partially and simultaneously affect the Indonesia Sharia Stock Index.